Faktor-Faktor yang Mempengaruhi Keputusan Jajan Sembarangan pada Anak di Sekolah Dasar Negeri Tengket 1 Kabupaten Bangkalan - Wahidah Sukriani; Itma Annah; Herlinadiyaningsih Herlinadiyaningsih; Siti Hapsah Pahira (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2021)
Abstract – Maintaining health from an early age is important to do. Nutrition has an important role in the growth and development of a child. The habit of eating snacks at school is a habit that almost all students do at school. However, the importance of children's snacks at school is not supported by the nutritional content in the food consumed by students. Objective: to find out the factors that influence the habit of random snacks in children. Methods: This research method uses descriptive quantitative research methods, using a cross section study research design with data collection techniques carried out using a random survey of 20 elementary school children. Results: (1) The breakfast variable has a positive and insignificant relationship, (2) the variable knowledge of nutrition in food and (3) bringing supplies to school has a negative and significant relationship to the decision to consume random snacks, (4) the influence of variables X1, X2 , and X3 to Y of 42.32% while 57.68% is influenced by other variables outside the model. Conclusion: The variables of knowledge (X2) and carrying provisions (X3) have a significant influence on reducing students' decisions to consume random snacks at school.